Severe anaphylaxis following administration of radiocontrast in patient undergoing coronary intervention - KC, Bishal; Gautam, Samir; Dhungel, Sachin; Khan, Mazhar; Shakya, Binesh (Journal of Advances in Internal Medicine, 2022)
Radiocontrast material is among the common drugs causing allergic reaction. Mostly it is well tolerated. The symptoms range from mild with urticaria to fatal anaphylaxis, developing rapidly. Anaphylaxis is the most severe form of radiocontrast media (RCM) induced hypersensitivity reaction. With more use of diagnostic and therapeutic procedure, the use of the radiocontrast media is increasing. We report here two cases of severe anaphylactic reaction that occurred during the coronary intervention for myocardial infarction.